Perceptual characteristics of Parkinsonian speech: a comparison of the pharmacological effects of levodopa across speech and non-speech motor systems. - Plowman-Prine EK; Okun MS; Sapienza CM; Shrivastav R; Fernandez HH; Foote KD; Ellis C; Rodriguez AD; Burkhead LM; Rosenbek JC (NeuroRehabilitation, 2009)
The purpose of this study was to: (1) define perceptual speech characteristics of idiopathic Parkinson disease (IPD) across 35 speech dimensions adapted from Darley et al. [19] and grouped under six speech-sign clusters (respiration, phonation, resonance, articulation, prosody and rate); (2) examine the effects of levodopa on the 35 perceptual speech dimensions and speech-sign clusters; and (3) to compare the relative effectiveness of levodopa on global motor functioning vs. speech production. Sixteen patients with IPD read the 'Grandfather Passage' both 'on' and 'off' levodopa. Three blinded speech-language pathologists performed perceptual speech analyses using a seven-point scale. The diagnosis of IPD was made by a movement disorders fellowship trained neurologist who applied UK Brain bank criteria and administered the Unified Parkinson Disease Rating Scale. Concordant with previous studies, the results of this experiment indicated that IPD disrupted multiple speech production subsystems, with prosody being the most severely affected domain. The perceptual dimensions that were most severely affected included: (1) sound imprecision; (2) mono-loudness; (3) mono-pitch; (4) reduced stress and (5) harsh voice. No significant differences were obtained between medicated states ('on'/'off') for any of the 35 individual speech dimensions and speech-sign clusters. Global motor function significantly improved following dopaminergic medications.